2022
DOI: 10.3390/su14148433
|View full text |Cite
|
Sign up to set email alerts
|

Recovering from Financial Implications of Flood Impacts—The Role of Risk Transfer in the West African Context

Abstract: In many West African river basins, households regularly experience floods and the associated impacts. In the absence of widely accessible formal risk transfer mechanisms (e.g., insurance), households often have to cope with financial impacts. Only a few studies have explored the financial effects of floods on agriculture-dependent households in the region and the role formal and informal risk transfer plays in their mitigation. This study addresses this gap, explores flood impacts with financial implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Jahns-Harms (2017) found that, through the access they provide to savings and social support, CSGs increase the capacity to face crises resulting from inflation, illness, and poor harvest, among other causes. Other works found that CSG participants take less time to recover from a crisis than non-participants (Wagner et al, 2022;Panman et al, 2022).…”
Section: Sustainability and Performancementioning
confidence: 98%
“…Jahns-Harms (2017) found that, through the access they provide to savings and social support, CSGs increase the capacity to face crises resulting from inflation, illness, and poor harvest, among other causes. Other works found that CSG participants take less time to recover from a crisis than non-participants (Wagner et al, 2022;Panman et al, 2022).…”
Section: Sustainability and Performancementioning
confidence: 98%